Weight-adjusted waist index and disability: a cohort study from CHARLS - Guangyan Liu; Tuming Zhang; Yueying Wu; Wenyue Sha; Liqi Chen; Jinhua Luo; Yu Yang (BMC, 2024)
Abstract Background The association between weight-adjusted waist index (WWI) and disability is unclear. This study aimed to assess the relationship between WWI and disability in middle-aged and elderly Chinese individuals and provide more predictive indicators for disability prevention. Methods In this study, 13,015 middle-aged and older adults aged 45 years and above who were surveyed in 2011 by the China Health and Aging Tracking Survey (CHARLS) database were selected, and 8344 respondents with complete data were included for cohort analysis after seven years of follow-up. Information on clinical demographic characteristics, anthropometric indices, assessment of disability, and related covariates were collected, and the presence or absence of disability was assessed by the disability scale. WWI was calculated by dividing the waist circumference (cm) by the square root of the body weight (kg). Cox proportional hazards model was used to analyze the association between WWI and disability after follow-up. Results Our study found that 2912 of 8344 participants had disability after seven years of follow-up, and disability incidence was approximately 34.9%. Age, sex, place of residence, chronic disease, depression, waist circumference, and WWI were significantly associated with disability in univariate analysis. Among them, there was a positive association between WWI as a continuous variable and incidence of disability (hazard ratio (HR) = 1.26, 95% CI: 1.22-1.31, p < 0.001). WWI was transformed into categorical variables using quartiles as cutoffs for disability regression analysis. After adjusting covariates, HR values in the 2nd, 3rd and 4th quantile showed an increasing trend compared with the 1st quantile, and the risk of disability among WWI subjects in the 4th quantile increased by 43% (95% CI: 1.24-1.64). P values for the trend test in the model were all < 0.001. In subgroup analyses, the positive association between WWI and risk of disability remained robust for sex, age, alcohol consumption, smoking status, education level, marital status, and place of residence after adjusting for all covariates considered in this study. Conclusions WWI is a new and reliable obesity-related indicator that can be used for disability prevention. WWI can be detected and controlled for reducing the risk of disability.